Role of cytochrome P-450 metabolites in the regulation of renal function and blood pressure in 2-kidney 1-clip hypertensive rats - Sporková, Alexandra; Kopkan, Libor; Varcabová, Šárka; Husková, Zuzana; Hwang, Sung Hee; Hammock, Bruce D; Imig, John D; Kramer, Herbert J; Červenka, Luděk (American journal of physiology. Regulatory, integrative and comparative physiology, 2011)
Alterations in renal function contribute to Goldblatt two-kidney, one-clip (2K1C) hypertension. A previous study indicated that bioavailability of cytochrome P-450 metabolites epoxyeicosatrienoic acids (EETs) is decreased while that of 20-hydroxyeicosatetraenoic acids (20-HETE) is increased in this model. We utilized the inhibitor of soluble epoxide hydrolase cis-4-[4-(3-adamantan-1-yl-ureido)-cyclohexyloxy]-benzoic acid (c-AUCB) and HET-0016, the inhibitor of 20-HETE production, to study the role of EETs and 20-HETE in the regulation of renal function. Chronic c-AUCB treatment significantly decreased systolic blood pressure (SBP) (133 ± 1 vs. 163 ± 3 mmHg) and increased sodium excretion (1.23 ± 0.10 vs. 0.59 ± 0.03 mmol/day) in 2K1C rats. HET-0016 did not affect SBP and sodium excretion. In acute experiments, renal blood flow (RBF) was decreased in 2K1C rats (5.0 ± 0.2 vs. 6.9 ± 0.2 ml·min(-1)·g(-1)). c-AUCB normalized RBF in 2K1C rats (6.5 ± 0.6 ml·min(-1)·g(-1)). HET-0016 also increased RBF in 2K1C rats (5.8 ± 0.2 ml·min(-1)·g(-1)). Although RBF and glomerular filtration rate (GFR) remained stable in normotensive rats during renal arterial pressure (RAP) reductions, both were significantly reduced at 100 mmHg RAP in 2K1C rats. c-AUCB did not improve autoregulation but increased RBF at all RAPs and shifted the pressure-natriuresis curve to the left. HET-0016-treated 2K1C rats exhibited impaired autoregulation of RBF and GFR. Our data indicate that c-AUCB displays antihypertensive properties in 2K1C hypertension that are mediated by an improvement of RBF and pressure natriuresis. While HET-0016 enhanced RBF, its anti-natriuretic effect likely prevented it from producing a blood pressure-lowering effect in the 2K1C model.
Keywords: Animals; epoxid hydrolasy; Kidney; Sodium; Regional Blood Flow; amidiny; Hydroxyeicosatetraenoic Acids; Amidines; Enzyme Inhibitors; kyseliny hydroxyeikosatetraenové; renovaskulární hypertenze; krevní tlak; kyseliny arachidonové; Male; modely nemocí na zvířatech; sodík; Hypertension, Renovascular; inhibitory enzymů; systém (enzymů) cytochromů P-450; Disease Models, Animal; regionální krevní průtok; krysa rodu Rattus; Arachidonic Acids; zvířata; mužské pohlaví; Blood Pressure; ledviny; Rats; Cytochrome P-450 Enzyme System; Epoxide Hydrolases